Heterotypic Multicellular Spheroids as Experimental and Preclinical Models of Sprouting Angiogenesis - Igor V. Vakhrushev; Elizaveta K. Nezhurina; Pavel A. Karalkin; Anastasia V. Tsvetkova; Nataliya S. Sergeeva; Alexander G. Majouga; Konstantin N. Yarygin (Biology, 2021)
Sprouting angiogenesis is the common response of live tissues to physiological and pathological angiogenic stimuli. Its accurate evaluation is of utmost importance for basic research and practical medicine and pharmacology and requires adequate experimental models. A variety of assays for angiogenesis were developed, none of them perfect. In vitro approaches are generally less physiologically relevant due to the omission of essential components regulating the process. However, only in vitro models can be entirely non-xenogeneic. The limitations of the in vitro angiogenesis assays can be partially overcome using 3D models mimicking tissue O2 and nutrient gradients, the influence of the extracellular matrix (ECM), and enabling cell-cell interactions. Here we present a review of the existing models of sprouting angiogenesis that are based on the use of endothelial cells (ECs) co-cultured with perivascular or other stromal cells. This approach provides an excellent in vitro platform for further decoding of the cellular and molecular mechanisms of sprouting angiogenesis under conditions close to the in vivo conditions, as well as for preclinical drug testing and preclinical research in tissue engineering and regenerative medicine.